Modelling satellite galaxies in semi-analytical models - Delfino, F. M. (2021)
Understanding the evolution of satellite halos is important in predicting the abundance of dark matter subhalos and satellite galaxies. However, in numerical simulations of structure formation, spurious disruptions can occur that make the halos of some galaxies no longer detectable. Those galaxies that have lost their host dark matter halo are called “orphan galaxies”. In this work, we consider a model for the evolution of the orbits of orphan galaxies, which takes into account the effects of both dynamical friction and tidal forces. We propose to use the two-point correlation function and the halo mass function of a high-resolution A-body simulation to constrain the free parameters of the model.